The Effect of Matching NIK as NPWP on Taxpayer Compliance: Income Tax OP Article 21 Employees at the Employment Social Security Organizing Agency in Greater Bandung - Bagus Darmawan Putra; Ibna Kamilia Fiel Afroh; Achmad Syahfrudin Zulkarnnaeni (Westscience Press, 2024)
This study aims to determine the effect of NIK matching as NPWP on Taxpayer Compliance (PPh OP Article 21 Employees at the Employment Social Security Organizing Agency in Besuki Raya)